Model checking for decision making behaviour of heterogeneous multi-agent autonomous system - Choi, Jiyoung (Cranfield University, 2013)
An autonomous system has been widely applied for various civil/military research because of its versatile capability of understanding high-level intent and direction of a surrounding environment and targets of interest. However, as autonomous systems can be out of control to cause serious loss, injury, or death in the worst case, the verification of their functionalities has got increasing attention. For that reason, this study is focused on the verification of a heterogeneous multi-agent autonomous system. The thesis first presents an overview of formal methods, especially focuses on model checking for autonomous systems verification. Then, six case studies are presented to verify the decision making behaviours of multi-agent system using two basic scenarios: surveillance and convoy. The initial system considered in the surveillance mission consists of a ground control system and a micro aerial vehicle. Their decision-making behaviours are represented by means of Kripke model and computational tree logic is used to specify the properties of this system. For automatic verification, MCMAS (Model Checker for Multi-Agent Systems) is adopted due to its novel capability to accommodate the multi-agent system. After that, the initial system is extended to include a substitute micro aerial vehicle. These initial case studies are then further extended based on SEAS DTC exemplar 2 dealing with behaviours of convoy protection. This case study includes now a ground control system, an unmanned aerial vehicle, and an unmanned ground vehicle. The MCMAS successfully verifies the targeting behaviours of the team-level unmanned systems. Reversely, these verification results help retrospectively improve the design of decision-making algorithms by considering additional agents and behaviours during four steps of scenario modification. Consequently, the last scenario deals with the system composed of a ground control system, two unmanned aerial vehicles, and four unmanned ground vehicles with fault-tolerant and communications relay capabilities. In conclusion, this study demonstrates the feasibility of model checking algorithms as a verification tool of a multi-agent system in an initial design stage. Moreover, this research can be an important first step of the certification of multi-agent autonomous systems for the domains of robotics, aerospace and aeronautics.
Keywords: Autonomous systems; Unmanned vehicles; Modelling